2020
DOI: 10.3390/ijerph17082808
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Toxicity of Tetracycline with Polystyrene Spheres on Gastric Cancer Cells

Abstract: Nowadays, microplastics (MPs) exist widely in the marine. The surface has strong adsorption capacity for antibiotics in natural environments, and the cytotoxicity of complex are poorly understood. In the study, 500 nm polystyrene (PS-MPs) and 60 nm nanoplastics (PS-NPs) were synthesized. The adsorption of PS to tetracycline (TC) was studied and their toxicity to gastric cancer cells (AGS) was researched. The adsorption experimental results show that PS absorbing capacity increased with increasing TC concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Similarly, concerning autophagy, a significant presence of autophagy vacuoles was observed in the enterocytes of planarians Dugesia japonica fed with polyethylene microsphere mixtures with a diameter ranging from 1 to 10 µm or 10-27 µm sized plastic particles [116]. Except for marine organisms and mammals, exposure to microparticles/plastics and specifically PS-MPs has led to apoptotic or autophagic cell death in human cell lines such as gastric cancer cells (AGS) after exposure to 500 nm and 60 nm polystyrene nanoplastics at concentrations 1, 5, 10, 50, and 100 mg L −1 [117] and macrophages [118].…”
Section: Molecular Events Apoptosis and Autophagymentioning
confidence: 99%
“…Similarly, concerning autophagy, a significant presence of autophagy vacuoles was observed in the enterocytes of planarians Dugesia japonica fed with polyethylene microsphere mixtures with a diameter ranging from 1 to 10 µm or 10-27 µm sized plastic particles [116]. Except for marine organisms and mammals, exposure to microparticles/plastics and specifically PS-MPs has led to apoptotic or autophagic cell death in human cell lines such as gastric cancer cells (AGS) after exposure to 500 nm and 60 nm polystyrene nanoplastics at concentrations 1, 5, 10, 50, and 100 mg L −1 [117] and macrophages [118].…”
Section: Molecular Events Apoptosis and Autophagymentioning
confidence: 99%
“…The average sizes of PS20 and PS200 were 29 and 212 nm, respectively. The hydrated particle size of PS in the medium was larger than that in deionized water probably because the nutrients in the medium could attach to their surface [35]. The TEM images clearly revealed that the virgin and uorescent PS with uniform shape and size (Fig.…”
Section: Characterization Of Psmentioning
confidence: 95%
“…Studies by Wang, Bai et al (2020) and Yu (2021) showed that 30 nm plastic particles penetrate the cell membrane and accumulate in the cytoplasm, while 100 nm plastic particles are easily adsorbed on the cell surface and edges, and have difficulty entering the cell. In addition, Yan et al (2020) found that after cell stimulation, protein rings formed on the surface, which reduced MP‐induced ROS production. However, this was not the case when high concentrations of MPs were tested.…”
Section: Oxidative Stress‐induced Toxicity Mechanism Of Mpsmentioning
confidence: 99%
“…Oxidative stress is a condition in which the oxidative and antioxidant reactions in the body are out of balance and this is more conducive to oxidation. To resist excessive ROS, cells produce oxidative stress responses for self‐protection (Yan et al, 2020), at which time, reactive oxygen radicals attack cells and tissues and cause damage (Chen & Zhong, 2014). Previous studies have shown that low concentrations of MPs cause oxidative stress in Eriocheir sinensis in a short time (Kan et al, 2022), oxidative stress induced by MPs has also been found to cause reproductive toxicity and other adverse events in mouse experiments (An et al, 2021; Li, Ma, et al, 2021; Xie et al, 2020).…”
Section: Oxidative Stress‐induced Toxicity Mechanism Of Mpsmentioning
confidence: 99%